RapTB: a lung-derived hemoglobin fragment with activity against Mycobacterium tuberculosis - Klevesath, Leonard; Noschka, Reiner; Vomhof, Thomas; Mohnani, Jacky; Grieshober, Mark; Michaelis, Jens; Walther, Paul; Rodriguez, Armando; Preising, Nico; Read, Clarissa; Wiese, Sebastian; Ständker, Ludger; et al. (Frontiers in Microbiology, 2025)
Tuberculosis (TB) remains difficult to treat due to the need for prolonged multidrug therapy and the global rise of drug-resistant Mycobacterium tuberculosis (Mtb) strains. Endogenous antimicrobial peptides (AMPs) have emerged as promising candidates for host-directed therapies. Given the pulmonary nature of TB, we hypothesized that human lung tissue contains peptides with intrinsic antimycobacterial activity. We screened a peptide library derived from human lung tissue and identified a 39-amino-acid C-terminal fragment of β-hemoglobin (HBB(112–147)), referred to as RapTB, with potent activity against Mtb. Recombinant RapTB exhibited dose-dependent inhibition of extracellular Mtb, reaching ~60% activity at 50 μM. Electron microscopy revealed mycobacterial cell wall disruption as a likely mechanism. RapTB was non-toxic to primary human macrophages and efficiently internalized by Mtb-infected cells. However, it did not co-localize with intracellular bacilli and failed to limit intracellular replication. HBB-derived fragments such as RapTB have previously been identified in human tissues and are known to exhibit broad-spectrum antimicrobial activity. Our findings extend this functional class to include antimycobacterial activity and suggest a potential role for RapTB in the early, extracellular phase of host defense against TB.